ANALYSIS AND DETERMINATION OF POSITION BATTALION COMMANDER AAL METHOD WITH PERSONALITY AND METHODS DEMATEL PAPI KOSTICK ANALYTIC NETWORK PROCESS (DFANP) - Didit Herdiawan; Agus Setiadji; Avando Bastari; Adi Bandono (JOURNAL ASRO, 2020)
Indonesian Naval Academy (AAL) is the educational institution that serves to educate Navy officer cadets into future leaders of the Navy to support the main tasks of the Navy in the future. Battalion Commander is a very important position in the organizational structure of the Naval Academy Midshipman educate. In military Commander Regulation no.138/XII/2011 confirms the necessity of each military personnel has soft and hard competencies. Therefore, this study focuses on the analysis and determination of criteria for the post of Batalyon commander of Naval Academy, includes soft and hard competencies and personality using PAPI Kostick, DEMATEL, ANP to get the best commander that is able to realize the basic tasks of the Navy. PAPI Kostick Personality Methods is a personality test on the employment situation. Along with other criteria such as Knowledge, Skills, Health, Phisic test, and Konduite, PAPI Kostick Personality criteria will be examined interrelationships among criteria and sub-criteria therein between using DEMATEL questionnaire. The results of DEMATEL is then drawn into a model of ANP. Furthermore structured questionnaire ANP. Then the results of questionnaires that have been processed, will be used as input in the software Superdecision. The results of the software is the weight of each sub-criteria that can be used in the assessment of the commander of selection . And in the example section assessment , the results of Superdecision software , it can be seen on the ranking of alternative commander’s candidate models have added alternative cluster .Keywords : Soft and Hard Competence, PAPI Kostick Personality, DEMATEL, and Analytic Network Process.